Assessment of metal levels in foodstuffs from the Region of Valencia (Spain). (2018) - Marín, Silvia; Pardo, Olga; Sánchez, Alfredo; Sanchis, Yovana; Vélez, Dinoraz; Devesa, Vicenta; Font, Guillermina; Yusà, Vicent
Graphical abstract: Highlights: Concentrations of metals were measured in a TDS carried out in 2010–2011 is presented. Levels were, in general, below the maximum levels set by the European legislation. It confirms a decreasing tendency when compared with other studies. Abstract: Concentrations of lead, mercury, cadmium, arsenic, tin, copper and chromium were measured in a study carried out in 2010–2011. A total of 8100 food samples were collected and composite samples for 12 food groups were analysed for metal concentration levels. Metal levels were, in general, below the maximum levels set by the current European legislation. The fish group presented the highest Cd, Hg and As levels, whereas sweeteners and condiments group was the most contaminated food group by Pb, Cr and Sn and the meat group had the highest concentrations of Cu. The results of this study are generally similar to or lower than those observed in other studies conducted in other countries, except in the case of Hg, for which high values were obtained, mainly in swordfish. In addition, this survey confirms a decreasing tendency when compared with other studies carried out in Spain.